Perbaikan dan Penguatan Keuangan Negara dalam Era Reformasi - Aqila, Bunga; Yuliani, Azka; Hasan, Kayladiva; Elvina, Vania (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
Regulation of state finances. The government has issued Law of the Republic of Indonesia Number 17 of 2003 Article 6, stating that: (1) The President as Head of Government holds the power to manage state finances as part of government power. (2) Powers as intended in paragraph (1): a). authorized to the Minister of Finance, as fiscal manager and Government Representative in the ownership of separated state assets; b). authorized to the minister/institution head as Budget User/Property User of the state ministry/institution he leads; c). handed over to the governor/regent/mayor as head of regional government to manage regional finances and represent the regional government in the ownership of separated regional assets. d). does not include authority in the monetary sector, which includes, among other things, issuing and circulating money, which is regulated by law. The aim of this research is to improve and strengthen state finances in a better era of reform. The research method is a normative juridical approach sourced from library data. The results of the research show that the government is taking various ways to strengthen and improve state finances by drafting the Bill and PNBP even though the mechanism for determining it is deemed inappropriate. In conclusion, the government must take a firm stance in making state financial revenues autonomous to avoid abuses committed by related institutions.